Shell-restrained pore-forming unit, and preparation method and application thereof
Patent Information
- Application Number
- CN202611166450.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-09
AI Technical Summary
然而,直接引入未包覆的有机或碳质造孔剂时,造孔剂在喷涂飞行和沉积过程中容易提前烧损,导致成孔位置和孔径分布难以稳定控制;过量或非受限的造孔剂还可能形成连通孔或贯穿孔道,影响涂层的力学完整性和服役稳定性
(1)通过碳质芯核、氧传递调节层和陶瓷骨架壳层协同构成壳层约束成孔单元,提高了孔腔位置及孔隙结构的可设计性,制备具有孔隙结构的隔热涂层,并降低了涂层的等效热导率。
Smart Images

Figure CN122878154A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a shell-constrained pore-forming unit, its preparation method and application, belonging to the field of thermal spraying heat-insulating coating technology. Background Technology
[0002] Zirconia-based thermal insulation coatings possess low thermal conductivity, high melting point, and good thermal stability, making them widely used on the surfaces of thermal protection and insulation components. For thermally sprayed zirconia-based coatings, interlaminar gaps, microcracks, and porosity affect the heat transfer path and significantly impact the coating's equivalent thermal conductivity. A suitable amount of porosity can increase the tortuosity of the heat conduction path, thereby helping to reduce the coating's equivalent thermal conductivity.
[0003] In related technologies, the porosity of ceramic coatings is typically controlled by adjusting spraying parameters, introducing pore-forming agents, or altering the powder structure. However, when uncoated organic or carbonaceous pore-forming agents are directly introduced, the agents are prone to premature burn-off during spraying and deposition, making it difficult to stably control the pore location and pore size distribution. Excessive or unrestricted pore-forming agents may also form interconnected pores or through-channels, affecting the mechanical integrity and service stability of the coating.
[0004] Therefore, how to reduce the premature consumption of carbonaceous pore-forming components during the thermal spraying process and to localize and form controllable cavities without relying on through channels is a key issue in improving the designability of coating pore structure. Summary of the Invention
[0005] To address the problems existing in related technologies, this invention provides a shell-constrained pore-forming unit, its preparation method, and its application. This invention involves sequentially setting an oxygen transfer regulating layer and a ceramic framework shell layer on the outside of a carbonaceous core, and using the resulting pore-forming unit to prepare zirconia-based composite granulated powder and a thermal insulation coating. This causes the carbonaceous core to undergo restricted oxidation or removal during subsequent heat treatment, forming cavities at the original carbonaceous core location. Simultaneously, through local sintering, necking, or interface closure of the ceramic framework shell layer and / or adjacent zirconia-based ceramic sheets, closed-pore, semi-closed-pore, or non-through-pore cavity structures are formed.
[0006] One objective of this invention is to provide a method for preparing a shell-constrained porous unit, comprising the following steps: S1: Disperse the carbon core in a solvent to form a carbon core dispersion; add a precursor salt for forming an oxygen transfer regulating layer to the carbon core dispersion to form a reaction dispersion system; adjust the pH of the reaction dispersion system and then heat the reaction; after the reaction is completed, the reaction product is obtained; the reaction product is separated into solid and liquid components; the solid product is washed, dried and subjected to a first heat treatment in sequence to obtain a carbon core with an oxygen transfer regulating layer on the outside.
[0007] S2: The carbonaceous core, which forms the oxygen transfer regulating layer on the outside in step S1, is dispersed in the ceramic skeleton shell precursor system. After stirring, drying and a second heat treatment, a ceramic skeleton shell is formed on the outside of the oxygen transfer regulating layer, resulting in a shell-constrained pore-forming unit consisting of a carbonaceous core, an oxygen transfer regulating layer and a ceramic skeleton shell, from the inside to the outside.
[0008] The ceramic framework shell is not a single cerium oxide shell, but is composed of one or more of yttrium-stabilized zirconium oxide, alumina, mullite, yttrium aluminum garnet, or rare earth zirconates.
[0009] Preferably, the carbon core in S1 is one or more of the following: carbon microspheres, graphite microspheres, carbon black agglomerated particles, resin carbonized microspheres, or phenolic resin carbonized particles; the particle size of the carbon core is 1~30μm; and the amount of carbon core added to the carbon core dispersion is 5~100g / L.
[0010] More preferably, the carbonaceous core in S1 is a carbon microsphere; the particle size of the carbonaceous core is 5~10μm; and the amount of carbonaceous core added in the carbonaceous core dispersion is 20g / L.
[0011] More preferably, the solvent S1 is one or a combination of water, an aqueous solution of anhydrous ethanol, or an aqueous solution of isopropanol.
[0012] More preferably, the amount of water added to the aqueous solution of anhydrous ethanol or isopropanol in S1 is 50-100% by volume.
[0013] The carbon core of S1 is a commercially available product and can be obtained through conventional commercial channels; the carbonized resin microspheres and carbonized phenolic resin particles are prepared by carbonizing the corresponding resin microspheres in an inert atmosphere. The carbonization temperature is 600~1000℃, the time is 1~4h, and the inert atmosphere is nitrogen or argon. The specific supplier and product brand of the carbon core do not constitute a limitation on the technical solution of this invention.
[0014] Preferably, the precursor salt in S1 is one or more of zirconium oxynitrate, zirconium oxychloride, zirconium acetate, cerium nitrate, cerium acetate, or yttrium nitrate; the total metal ion concentration of the precursor salt in the reaction dispersion system is 0.02~1.0 mol / L; based on the mass of the oxide theoretically formed in the first heat treatment of the precursor salt, the mass ratio of the oxide to the carbonaceous core is 0.05:1~1.5:1; the pH value of the reaction dispersion system is 8~10; the heating reaction temperature is 90~120℃, and the heating reaction time is 6~12h; the temperature of the first heat treatment is 300~450℃, and the time is 0.5~2h; the oxygen transfer regulating layer is one or more of cerium oxide, zirconium oxide, cerium-zirconium composite oxide, yttrium-stabilized zirconium oxide, doped cerium oxide, or doped zirconium oxide; the thickness of the oxygen transfer regulating layer is 0.05~1μm.
[0015] More preferably, the mass ratio of oxide to carbonaceous core in S1, based on the mass of oxide formed according to the precursor salt theory, is 0.5:1 to 1.5:1.
[0016] More preferably, the precursor salt in S1 is one or a combination of zirconium oxynitrate, yttrium nitrate, and cerium nitrate; the pH value of the reaction dispersion system is 9; the heating reaction temperature is 100°C and the heating reaction time is 8h; the temperature of the first heat treatment is 350°C and the time is 1h; and the thickness of the oxygen transfer regulating layer is 0.30~0.35μm.
[0017] More preferably, the precursor salt in S1 is a zirconium salt, cerium salt, yttrium salt, and / or doped element salt that can form an oxygen transfer regulating layer through hydrolysis, precipitation, and / or thermal decomposition.
[0018] Preferably, the ceramic framework shell precursor system in S2 is a combination of one or more of ceramic sol and ceramic nanoparticle dispersion. The ceramic sol is a combination of one or more of yttrium oxide-stabilized zirconia sol, alumina sol, silica sol, yttrium oxide sol, zirconia sol, lanthanum oxide sol, gadolinium oxide sol, samarium oxide sol, or ytterbium oxide sol; the ceramic nanoparticles in the ceramic nanoparticle dispersion are a combination of one or more of yttrium oxide-stabilized zirconia, alumina, mullite, yttrium aluminum garnet, or rare earth zirconate nanoparticles with an average particle size of 10-200 nm; in the ceramic framework shell precursor system, the content of the dispersed phase is 1-30% by mass, with the remainder being... The dispersion medium; the carbonaceous core forming the oxygen transfer regulating layer on the outside is dispersed in the ceramic skeleton shell precursor system at a mass ratio of 1:0.1 to 1:5 of the carbonaceous core forming the oxygen transfer regulating layer on the outside to the ceramic solid component in the ceramic skeleton shell precursor system; the stirring, drying and second heat treatment conditions are as follows: stirring for 0.5 to 12 hours, drying at 60 to 120°C for 2 to 12 hours, and then performing a second heat treatment at 300 to 700°C for 0.5 to 4 hours; the thickness of the ceramic skeleton shell of the shell-constrained pore-forming unit is 0.2 to 5 μm.
[0019] More preferably, in step S2, yttrium-stabilized zirconia sol is used as the ceramic sol, and alumina nanoparticle dispersion is used as the ceramic nanoparticle dispersion. The yttrium-stabilized zirconia sol uses yttrium-stabilized zirconia colloidal particles as the dispersed phase, with a Y₂O₃ content of 6-8% by mass, and the remainder being ZrO₂ and unavoidable impurities. The dispersion medium for the yttrium-stabilized zirconia sol is deionized water, and the solid content of the yttrium-stabilized zirconia sol is 20% by mass (i.e., the amount of yttrium-stabilized zirconia added to the yttrium-stabilized zirconia sol is 20% by mass). The alumina nanoparticle dispersion is formed by dispersing alumina nanoparticles with an average particle size of 50 nm in deionized water, and the amount of alumina nanoparticles added to the alumina nanoparticle dispersion is 20% by mass.
[0020] In the ceramic framework shell precursor system, the contents of yttrium oxide stabilized zirconia colloidal particles and alumina particles are both 20% by mass percentage, with the remainder being a dispersion medium.
[0021] More preferably, the S2 drying temperature is 80℃ and the drying time is 8h; the second heat treatment temperature is 500℃ and the time is 2h; the thickness of the ceramic skeleton shell is 1.5μm; and the ceramic skeleton shell is a YSZ-Al2O3 composite ceramic skeleton shell.
[0022] More preferably, the second heat treatment S2 is carried out in a nitrogen atmosphere.
[0023] More preferably, the ceramic skeleton shell is one or more of 8YSZ, YSZ-Al2O3 composite ceramic, YSZ-mullite composite ceramic, YSZ-yttrium aluminum garnet composite ceramic or rare earth zirconate composite ceramic.
[0024] The second objective of this invention is to provide a shell-constrained pore-forming unit prepared by the method of this invention, wherein the shell-constrained pore-forming unit comprises, from the inside to the outside, a carbonaceous core, an oxygen transfer regulating layer disposed outside the carbonaceous core, and a ceramic skeleton shell disposed outside the oxygen transfer regulating layer.
[0025] More preferably, the carbonaceous core is used to provide the location for cavity formation; the oxygen transfer regulating layer is used to regulate the oxygen transfer process to the carbonaceous core; and the ceramic skeleton shell is used to provide thermal shielding and spatial constraint, and participate in the subsequent cavity wall formation and local necking or interface closure.
[0026] The third objective of this invention is to provide a method for preparing a zirconia-based thermal insulation coating using a shell-constrained pore-forming unit, comprising the following steps: (1) Preparation of composite granulated powder: The shell-constrained pore-forming unit, zirconia-based heat insulation powder, binder and solvent are dispersed together to form a spray granulation slurry. The spray granulation slurry is sprayed and granulated to obtain zirconia-based composite granulated powder containing shell-constrained pore-forming unit.
[0027] (2) Spraying treatment: The zirconia-based composite granulated powder obtained in step (1) is fed into plasma spraying as a single composite spraying powder stream and deposited on the substrate surface to form a zirconia-based ceramic coating containing shell-constrained pore-forming units.
[0028] (3) Staged heat treatment: The zirconia-based ceramic coating obtained in step (2) is subjected to staged heat treatment to obtain a zirconia-based heat insulation coating with closed-pore, semi-closed-pore or non-through-pore cavity structure.
[0029] Preferably, the zirconia-based thermal insulation powder in step (1) is one or more of yttrium-stabilized zirconia powder, cerium-stabilized zirconia powder, and rare earth zirconate powder; the yttrium-stabilized zirconia powder contains 6-8% Y₂O₃ by mass, with the remainder being ZrO₂ and unavoidable impurities; the spray-granulation slurry contains 30-70% solids by mass, with the remainder being solvent; the solids content in the spray-granulation slurry is the percentage of the total mass of the shell-constrained pore-forming unit and the zirconia-based thermal insulation powder to the total mass of the spray-granulation slurry; taking the total mass of the shell-constrained pore-forming unit and the zirconia-based thermal insulation powder as 100%, the shell-constrained pore-forming unit accounts for 1-10% of the total mass of the shell-constrained pore-forming unit and the zirconia-based thermal insulation powder. The remainder is zirconia-based thermal insulation powder; the amount of binder added to the spray granulation slurry is 0.5-5% of the total mass of the shell-constrained pore-forming unit and the zirconia-based thermal insulation powder; the binder is not included in the solid content; the binder is one or more of polyvinyl alcohol, polyvinylpyrrolidone, or carboxymethyl cellulose; the dispersion method of the shell-constrained pore-forming unit, zirconia-based thermal insulation powder, binder, and solvent is one of drum premixing, low-energy ball milling premixing, wet dispersion, or slurry dispersion; the inlet air temperature of the spray granulation is 180-250℃, the outlet air temperature is 70-120℃, the atomization pressure is 0.2-1.0MPa, and the slurry feed rate is 5-100mL / min; the particle size of the zirconia-based composite granulated powder is 15-100μm.
[0030] More preferably, in step (1), the powder solid content of the spray granulation slurry is 50% by mass percentage, with the remainder being solvent; the shell-constrained pore-forming unit accounts for 3-5% of the total mass of the shell-constrained pore-forming unit and the zirconia-based heat-insulating powder, with the remainder being zirconia-based heat-insulating powder; the amount of binder added in the spray granulation slurry is 2% of the total mass of the shell-constrained pore-forming unit and the zirconia-based heat-insulating powder; the binder is polyvinyl alcohol; the inlet air temperature of the spray granulation is 200℃, the outlet air temperature is 90℃, the atomization pressure is 0.5MPa, and the slurry feeding rate is 20mL / min; the particle size of the zirconia-based composite granulated powder is 20-75μm.
[0031] More preferably, in step (1), the low-energy mixing temperature is 10~40℃ and the time is 0.5~4h; when using drum premixing, the rotation speed is 10~60rpm; when using low-energy ball mill premixing, the rotation speed is 50~150rpm, the ball material ratio is 1:1~5:1, and the ball milling time is 0.5~3h.
[0032] In the composite granulated powder, the shell-constrained pore-forming unit is embedded or partially embedded in the interior of the agglomerated particles and / or at the boundaries of the agglomerated particles by zirconia-based thermal insulation powder, and the carbonaceous core is not directly exposed on the outer surface of the agglomerated particles.
[0033] Preferably, the plasma spraying power in step (2) is 20~45kW, the spraying distance is 80~120mm, and the powder feeding rate is 10~80g / min; the substrate is one of nickel-based alloy, iron-based alloy, titanium alloy or ceramic matrix composite material.
[0034] More preferably, the plasma spraying power of step (2) is 30kW, the spraying distance is 100mm, and the powder feeding rate is 30g / min; the substrate is a nickel-based alloy.
[0035] Preferably, step (3) includes a first stage of oxidation pore-forming treatment and a second stage of necking treatment; the temperature of the first stage of oxidation pore-forming treatment is 400~750℃ and the time is 0.5~10h; the temperature of the second stage of necking treatment is 700~1100℃ and the time is 0.5~5h.
[0036] More preferably, the temperature of the first stage oxidation pore-forming treatment in step (3) is 450~500℃ and the time is 2~4h; the temperature of the second stage neck-sealing treatment is 850~900℃ and the time is 1~2h.
[0037] More preferably, the first stage of oxidation pore-forming treatment in step (3) is carried out in an air atmosphere.
[0038] More preferably, the second stage of neck sealing in step (3) is carried out in an inert atmosphere (such as a nitrogen atmosphere).
[0039] More preferably, the temperature of the first stage oxidation pore-forming treatment in step (3) is lower than the temperature of the second stage necking treatment.
[0040] In step (3), the first stage involves at least partial oxidation or removal of the carbon core, and the formation of a cavity at the original carbon core location; the second stage involves local sintering, necking, or interface closure of the ceramic skeleton shell and / or adjacent zirconia-based ceramic sheets.
[0041] The ceramic skeleton shell has thermal spray compatibility with the zirconia-based thermal insulation powder, meaning that the ceramic skeleton shell can be co-deposited or retained in the coating with the zirconia-based thermal insulation powder during plasma spraying and subsequent heat treatment, and does not form a low-melting-point phase, volatile phase, or continuous brittle reaction layer that significantly weakens the integrity of the ceramic skeleton of the coating.
[0042] The fourth objective of this invention is to provide a composite granulated powder prepared using the method of this invention.
[0043] More preferably, the outer surface of the composite granulated powder agglomerates is covered by a zirconia-based heat-insulating powder forming an outer coating region, and the shell-constrained pore-forming unit is located inside the outer coating region or adjacent to the outer coating region; the equivalent particle size of the shell-constrained pore-forming unit is smaller than the median particle size of the composite granulated powder agglomerates, and a single composite granulated powder agglomerates contains one or more shell-constrained pore-forming units.
[0044] The fifth objective of this invention is to provide a zirconia-based thermal insulation coating that can be appropriately prepared using the method of this invention. The zirconia-based thermal insulation coating comprises zirconia-based ceramic sheets and closed-cell, semi-closed-cell, or non-penetrating pore structures distributed between and / or within the zirconia-based ceramic sheets. The pore structures are constrained by a ceramic framework shell and / or zirconia-based ceramic sheets, and are formed by in-situ oxidation or removal of the carbonaceous core in the pore unit constrained by the shell. The pore structures do not penetrate along the thickness direction of the zirconia-based thermal insulation coating. Ceramic framework shell material is retained around the pores, and localized sintering necks and / or interface closure regions are formed between the ceramic framework shell and adjacent zirconia-based ceramic sheets. The present invention has the following beneficial effects: (1) By using a carbon core, an oxygen transfer regulating layer and a ceramic skeleton shell to form a shell-constrained pore unit, the designability of the pore location and pore structure is improved, a thermal insulation coating with a pore structure is prepared, and the equivalent thermal conductivity of the coating is reduced.
[0045] (2) The oxygen transfer regulating layer and the ceramic skeleton shell can regulate the oxidation process of the carbon core and reduce its tendency to be consumed prematurely during the spraying process.
[0046] (3) By using composite spray granulation, the pore-forming unit is embedded or partially embedded by zirconia-based heat-insulating powder, thereby improving the structural stability of the pore-forming unit during mixing, powder feeding and spraying processes.
[0047] (4) By performing staged heat treatment, the holes are formed first and then the neck is sealed, forming closed holes, semi-closed holes or non-through holes, reducing the tendency to form through holes.
[0048] (5) The formed cavity structure can increase the tortuousness of the heat flow transfer path, which is beneficial to reducing the equivalent thermal conductivity of the coating. Attached Figure Description
[0049] Figure 1 This is a schematic diagram of the shell-constrained pore-forming unit structure in Embodiment 1 of the present invention.
[0050] Figure 2 This is a schematic diagram of the cavity and necking structure in the zirconia-based coating after staged heat treatment in Embodiment 1 of the present invention. Detailed Implementation
[0051] To better illustrate the purpose, technical solution, and advantages of this invention, the following detailed description will be provided in conjunction with specific embodiments. In the embodiments and comparative examples of this invention, unless otherwise specified, all chemical reagents are commercially available analytical grade reagents. The carbon microspheres used in the embodiments and comparative examples of this invention are all commercially available products, obtainable through conventional commercial channels; their specific suppliers and product brands do not constitute a limitation on the technical solution of this invention. The yttrium-stabilized zirconia sol used in the embodiments and comparative examples of this invention is an aqueous sol with deionized water as the dispersion medium, yttrium-stabilized zirconia colloidal particles as the dispersed phase, and the solid content of the yttrium-stabilized zirconia colloidal particles is 20% (by mass percentage). The Y2O3 content in the yttrium-stabilized zirconia colloidal particles is 7% (by mass percentage), with the remainder being ZrO2 and unavoidable impurities. The alumina nanoparticle dispersion used is an aqueous dispersion with deionized water as the dispersion medium, and alumina nanoparticles with an average particle size of 50 nm as the dispersed phase. The amount of alumina nanoparticles added in the alumina nanoparticle dispersion is 20% (by mass percentage) (i.e., the solid content is 20% by mass percentage).
[0052] Example 1 A method for fabricating a shell-constrained porous unit includes the following steps: S1: Weigh 10.0 g of commercially available carbon microspheres with an average particle size of 10 μm and add them to a mixed solvent consisting of 250 mL of anhydrous ethanol and 250 mL of deionized water to form a dispersion with a carbon microsphere concentration of 0.020 g / mL. Under stirring conditions, add 94.0 mL of a 0.5 mol / L zirconium oxynitrate aqueous solution and 7.7 mL of a 0.5 mol / L yttrium nitrate aqueous solution to the dispersion. The concentration of the zirconium oxynitrate aqueous solution is expressed as the molar concentration of Zr, and the concentration of the yttrium nitrate aqueous solution is expressed as the molar concentration of Y. The precursor salt forms an oxide after the reaction, with a theoretical mass of approximately 6.2 g, of which the content of Y2O3 is approximately 7% by mass, and the remainder is ZrO2 and unavoidable impurities. Based on the mass of the oxide theoretically formed during the first heat treatment of the precursor salt, the mass ratio of oxide to carbon microspheres is approximately 0.62:1. The pH of the reaction dispersion system is adjusted to 9.0 using 10% ammonia water, and then transferred to a closed reaction vessel and reacted at 100°C for 8 h. After the reaction, centrifugation is performed, and the product is washed sequentially with deionized water and anhydrous ethanol. The resulting solid product is dried at 80°C for 8 h, and then kept at 350°C for 1 h in a nitrogen atmosphere to form a yttrium oxide-stabilized zirconium oxide oxygen transfer regulating layer with a thickness of approximately 0.30 μm on the outside of the carbon microspheres.
[0053] S2: 20.0 g of yttrium-stabilized zirconia sol (20% by mass) and 5.0 g of alumina nanoparticle dispersion (20% by mass) are mixed to obtain a ceramic framework shell precursor system containing 4.0 g of yttrium-stabilized zirconia solid and 1.0 g of alumina solid. The total mass of this ceramic framework shell precursor system is 25.0 g, the total mass of the ceramic solid component is 5.0 g, and its solid content is 20% by mass. Based on theoretical mass, an oxygen transfer regulating layer is formed on the outer side obtained in step S1. The carbon microspheres weigh approximately 16.2 g. The carbon core with an outer oxygen transfer regulating layer is dispersed in the ceramic framework shell precursor system at a mass ratio of 1:0.31 between the carbon core with the outer oxygen transfer regulating layer and the ceramic solid component in the precursor system. The mixture is stirred at 25 °C for 2 h, then dried at 80 °C for 8 h, and then heat-treated at 500 °C for 2 h in a nitrogen atmosphere. A YSZ-Al2O3 composite ceramic framework shell with a thickness of approximately 1.5 μm is formed on the outside of the oxygen transfer regulating layer, resulting in a shell-constrained pore-forming unit.
[0054] like Figure 1 As shown, the shell-constrained pore-forming unit comprises, from the inside out, a carbonaceous core, an oxygen transport regulating layer, and a ceramic framework shell.
[0055] The preparation of a zirconia-based thermal insulation coating using the shell-constrained pore-forming unit prepared in Example 1 includes the following steps: (1) Preparation of composite granulation powder: Weigh 3.0g of shell-constrained pore-forming unit and 97.0g of 8YSZ thermal insulation powder, and mix them at low energy for 2h at 25℃ and 40rpm to obtain a mixed powder; add 40.0g of 5% (mass percentage concentration) polyvinyl alcohol aqueous solution and 60.0g of deionized water to the mixed powder to form a spray granulation slurry; the actual amount of polyvinyl alcohol added is 2.0g, accounting for 2% of the total mass of the mixed powder (based on the total mass of the mixed powder being 100%), and polyvinyl alcohol is not included in the solid content; the solid content in the spray granulation slurry is the percentage of the total mass of the shell-constrained pore-forming unit and 8YSZ thermal insulation powder to the total mass of the spray granulation slurry, and the solid content of the spray granulation slurry is expressed as a mass percentage. 50%; Spray granulation was carried out under the conditions of inlet air temperature of 200℃, outlet air temperature of 90℃, atomization pressure of 0.5MPa and slurry feed rate of 20mL / min; after granulation, the zirconia-based composite granulated powder with a particle size of 20~75μm was obtained; in the obtained composite granulated powder, the shell-constrained pore-forming unit was embedded or semi-embedded by 8YSZ thermal insulation powder inside the agglomerated particles and / or at the boundaries of the agglomerated particles, and the carbonaceous core was not directly exposed on the outer surface of the agglomerated particles.
[0056] (2) Spraying treatment: Inconel 625 nickel-based alloy is used as the substrate; before spraying, the substrate surface is roughened by alumina sand so that the arithmetic mean roughness Ra of the substrate surface is about 4~6μm; zirconia-based composite granulated powder is sent into the plasma jet as a single composite spraying powder stream and deposited on the substrate surface under the conditions of spraying power of 30kW, spraying distance of 100mm and powder feeding rate of 30g / min to form a zirconia-based ceramic coating with shell-constrained pore-forming units.
[0057] (3) Staged heat treatment: In the first stage, the carbon core is kept at 500℃ for 2 hours in an air atmosphere to cause restricted oxidation or removal, and to form cavities at the original carbon core position; In the second stage, the ceramic skeleton shell and / or adjacent zirconia-based ceramic sheets are kept at 900℃ for 1 hour to cause local sintering, necking or interface closure, so as to obtain a zirconia-based heat insulation coating with closed pore, semi-closed pore or non-through pore cavity structure.
[0058] For example Figure 2 As shown, cavities are formed at the original carbonaceous core location, and the ceramic skeleton shell and / or adjacent zirconia-based ceramic sheets are necked or have interface closures at local locations.
[0059] Example 2 A method for preparing a shell-constrained porous unit, wherein this embodiment uses cerium-zirconium composite oxide as an oxygen transfer regulating layer, includes the following steps: S1: Weigh 10.0 g of commercially available carbon microspheres with an average particle size of 10 μm and disperse them in a mixed solvent of 250 mL anhydrous ethanol and 250 mL deionized water to form a dispersion with a carbon microsphere concentration of 0.020 g / mL. Under stirring conditions, add 40.6 mL of a 0.5 mol / L cerium nitrate aqueous solution and 40.6 mL of a 0.5 mol / L zirconium oxynitrate aqueous solution to the dispersion. The cerium nitrate aqueous solution is prepared using cerium nitrate hexahydrate, with the concentration expressed as the molar concentration of Ce, and the zirconium oxynitrate aqueous solution is expressed as the molar concentration of Zr. The molar ratio of Ce to Zr is 1:1. The theoretically formed oxide mass of the above precursor is approximately 6.0 g. Based on the theoretically formed oxide mass during the first heat treatment of the precursor salt, the mass ratio of the oxide to the carbon microspheres is approximately 0.60:1. The pH of the reaction dispersion system was adjusted to 9.0 using 10% ammonia solution, and then transferred to a closed reaction vessel for reaction at 100°C for 8 hours. After the reaction, the mixture was centrifuged and washed sequentially with deionized water and anhydrous ethanol. The resulting solid product was dried at 80°C for 8 hours and then kept at 350°C for 1 hour in a nitrogen atmosphere to form a cerium-zirconium composite oxide oxygen transfer regulating layer with a thickness of about 0.35 μm on the outside of the carbon microspheres.
[0060] S2: 20.0 g of yttrium-stabilized zirconia sol (20% by mass) and 5.0 g of alumina nanoparticle dispersion (20% by mass) were mixed to obtain a ceramic framework-shell precursor system containing 4.0 g of yttrium-stabilized zirconia solid and 1.0 g of alumina solid. The total mass of this ceramic framework-shell precursor system was 25.0 g, and the total mass of the ceramic solid component was 5.0 g, with a solid content of 20% by mass. Based on theoretical mass, the carbon microspheres with the oxygen transfer regulating layer on the outside obtained in step S1 have a mass of approximately 16.0 g. The carbon core with the oxygen transfer regulating layer on the outside is dispersed in the ceramic framework shell precursor system at a mass ratio of 1:0.31 between the carbon core with the oxygen transfer regulating layer on the outside and the ceramic solid component in the ceramic framework shell precursor system. The mixture is stirred at 25°C for 2 h, dried at 80°C for 8 h, and then heat-treated at 500°C for 2 h in a nitrogen atmosphere. A YSZ-Al2O3 composite ceramic framework shell with a thickness of approximately 1.5 μm is formed on the outside of the oxygen transfer regulating layer, thus obtaining a shell-constrained pore-forming unit.
[0061] Tests showed that the shell-constrained pore-forming unit prepared in this embodiment includes, from the inside out, a carbonaceous core, an oxygen transfer regulating layer, and a ceramic skeleton shell.
[0062] A zirconia-based thermal insulation coating was prepared using the shell-constrained pore-forming unit prepared in Example 2. Composite granulation powder was prepared using 3.0 g of the shell-constrained pore-forming unit and 97.0 g of 8YSZ thermal insulation powder. The low-energy mixing, spray granulation, plasma spraying, and staged heat treatment conditions were the same as in Example 1.
[0063] Tests showed that the original carbonaceous core of the coating prepared in this embodiment formed a cavity, and the ceramic skeleton shell and / or adjacent zirconia-based ceramic sheets were locally necked or closed at the interface.
[0064] Example 3 A method for fabricating a shell-constrained porous unit includes the following steps: S1: Weigh 10.0 g of commercially available carbon microspheres with an average particle size of 5 μm and disperse them in a mixed solvent of 250 mL anhydrous ethanol and 250 mL deionized water to form a dispersion with a carbon microsphere concentration of 0.020 g / mL. Under stirring conditions, add 188.0 mL of a 0.5 mol / L zirconium oxynitrate aqueous solution and 15.4 mL of a 0.5 mol / L yttrium nitrate aqueous solution to the dispersion. The concentration of the zirconium oxynitrate aqueous solution is expressed as the molar concentration of Zr, and the concentration of the yttrium nitrate aqueous solution is expressed as the molar concentration of Y. The theoretically formed oxide mass of the above precursor is approximately 12.4 g, of which the Y2O3 content is approximately 7% by mass, with the remainder being ZrO2 and unavoidable impurities. Based on the theoretically formed oxide mass in the first heat treatment of the precursor salt, the mass ratio of oxide to carbon microspheres is approximately 1.24:1. The pH of the reaction dispersion system was adjusted to 9.0 using 10% ammonia solution, and then transferred to a closed reaction vessel for reaction at 100°C for 8 hours. After the reaction, the mixture was centrifuged and washed sequentially with deionized water and anhydrous ethanol. The resulting solid product was dried at 80°C for 8 hours and then kept at 350°C for 1 hour in a nitrogen atmosphere to form a yttrium oxide-stabilized zirconia oxygen transfer regulating layer with a thickness of approximately 0.30 μm on the outside of the carbon microspheres.
[0065] S2: Mix 40.0g of yttrium-stabilized zirconia sol with a solid content of 20% by mass and 10.0g of alumina nanoparticle dispersion with a solid content of 20% by mass to obtain a ceramic framework shell precursor system containing 8.0g of yttrium-stabilized zirconia solid and 2.0g of alumina solid; the total mass of the ceramic framework shell precursor system is 50.0g, the total mass of the ceramic solid component is 10.0g, and its solid content is 20% by mass. Based on theoretical mass, the carbon microspheres with the oxygen transfer regulating layer on the outside obtained in step S1 have a mass of approximately 22.4 g. The carbon core with the oxygen transfer regulating layer on the outside is dispersed in the ceramic framework shell precursor system at a mass ratio of 1:0.45 between the carbon core with the oxygen transfer regulating layer on the outside and the ceramic solid component in the ceramic framework shell precursor system. The mixture is stirred at 25°C for 2 h, dried at 80°C for 8 h, and then heat-treated at 500°C for 2 h in a nitrogen atmosphere. A YSZ-Al2O3 composite ceramic framework shell with a thickness of approximately 1.5 μm is formed on the outside of the oxygen transfer regulating layer, thus obtaining a shell-constrained pore-forming unit.
[0066] Tests showed that the shell-constrained pore-forming unit prepared in this embodiment consists of a carbon core, an oxygen transfer regulating layer, and a ceramic skeleton shell, from the inside out.
[0067] A zirconia-based thermal insulation coating was prepared using the shell-constrained pore-forming unit prepared in Example 3. 5.0 g of the shell-constrained pore-forming unit and 95.0 g of 8YSZ thermal insulation powder were weighed and mixed at low energy for 2 hours at 25°C and a drum speed of 40 rpm. The amount of polyvinyl alcohol added was 2% of the total mass of the two powders (based on a total mass of 100%), and the powder solids content of the spray-granulated slurry was 50% by mass. All other conditions were the same as in Example 1.
[0068] Tests showed that the original carbonaceous core of the coating prepared in this embodiment formed cavities, and the ceramic skeleton shell and / or adjacent zirconia-based ceramic sheets were locally necked or had interface closures.
[0069] Example 4 In this embodiment, the preparation conditions of the shell-constrained pore-forming unit, composite granulation powder, and zirconia-based ceramic coating are the same as in Example 1, except that the staged heat treatment conditions are different.
[0070] Tests showed that the shell-constrained pore-forming unit prepared in this embodiment consists of a carbon core, an oxygen transfer regulating layer, and a ceramic skeleton shell, from the inside out.
[0071] The first stage involves holding the material at 450°C for 4 hours in an air atmosphere; the second stage involves holding the material at 850°C for 2 hours in a nitrogen atmosphere, resulting in a zirconia-based heat-insulating coating with closed-cell, semi-closed-cell, or non-through-cell structures.
[0072] Tests showed that the original carbonaceous core of the coating prepared in this embodiment formed a cavity, and the ceramic skeleton shell and / or adjacent zirconia-based ceramic sheets were locally necked or closed at the interface.
[0073] Comparative Example 1 This comparative example does not include a carbonaceous core, nor does it prepare shell-constrained pore-forming units. 100.0 g of 8YSZ thermal insulation powder was weighed, and a zirconia-based ceramic coating was prepared according to the same binder dosage, slurry powder solid content, spray granulation conditions, plasma spraying conditions, and staged heat treatment conditions as in Example 1.
[0074] Due to the lack of a carbonaceous core, the coating lacks localized pore-forming sources that can be oxidized or removed in situ. The pores mainly originate from the gaps between layers, incompletely bonded areas, or process pores formed during the thermal spraying process. It is difficult to pre-control the position and size of the pores by adjusting the particle size, content, and distribution of the pore-forming units.
[0075] Comparative Example 2 This comparative example uses commercially available carbon microspheres with an average particle size of 10 μm, but without adding zirconium oxynitrate and yttrium nitrate, and without forming an oxygen transfer regulating layer on the outside of the carbon microspheres. Instead, the carbon microspheres are directly added to the ceramic framework shell precursor system described in Example 1 to form a porous unit consisting only of a carbonaceous core and a ceramic framework shell. The remaining conditions are the same as in Example 1.
[0076] Due to the lack of an oxygen transfer regulating layer, the transfer of oxygen to the carbonaceous core mainly depends on defects in the ceramic skeleton shell, interlamellar gaps, or local open channels. The oxidation or removal rate of the carbonaceous core is not easy to adjust, which is not conducive to controlling the cavity formation process and size distribution.
[0077] Comparative Example 3 In this comparative example, a yttrium oxide-stabilized zirconia oxygen transport modulating layer was formed on the outside of the carbon microspheres according to the method of Example 1, but no outer ceramic framework shell was formed. All other conditions were the same as in Example 1.
[0078] Due to the lack of a ceramic framework shell, the carbonaceous core and oxygen transfer regulating layer lack thermal shielding and spatial constraint during mixing, spray granulation, plasma spraying and deposition, and the carbonaceous core is easily consumed prematurely; in the subsequent heat treatment process, there is also a lack of a ceramic shell that participates in the formation of cavity walls and the sealing of pores, which is not conducive to the formation of non-penetrating cavity structures constrained by ceramic walls.
[0079] Comparative Example 4 This comparative example prepared shell-constrained pore-forming units, composite granulated powder, and zirconia-based ceramic coatings according to the method of Example 1. The difference is that instead of using staged heat treatment, a single heat treatment of 2 hours was performed at 850°C in an air atmosphere.
[0080] Since the oxidation or removal of the carbonaceous core occurs simultaneously with the sintering and necking processes of the ceramic skeleton shell and adjacent zirconia-based ceramic sheets, it is difficult to achieve sequential control of pore formation followed by necking, which is not conducive to controlling the cavity morphology, opening channels and necking position.
[0081] The structural and process analysis of the above comparative examples shows that the carbonaceous core provides the location for in-situ cavity formation, the oxygen transfer regulating layer controls the oxygen transfer process to the carbonaceous core, the ceramic skeleton shell provides thermal shielding, spatial constraint, and the basis for subsequent cavity wall formation, and the staged heat treatment achieves sequential control of pore formation followed by necking. The synergy of these structures and processes facilitates the localized formation of closed-cell, semi-closed-cell, or non-penetrating cavity structures in zirconia-based thermal insulation coatings, improves the designability of the pore structure, and helps reduce the equivalent thermal conductivity of the coating.
[0082] The above embodiments and comparative examples are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Any equivalent substitutions, parameter adjustments, or changes in material combinations made based on the technical concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a shell-constrained porous unit, characterized in that, Includes the following steps: S1: Disperse the carbon core in a solvent to form a carbon core dispersion; add a precursor salt for forming an oxygen transfer regulating layer to the carbon core dispersion to form a reaction dispersion system; adjust the pH of the reaction dispersion system and then heat the reaction; after the reaction is completed, the reaction product is obtained; the reaction product is separated into solid and liquid components; the solid product is washed, dried and subjected to a first heat treatment in sequence to obtain a carbon core with an oxygen transfer regulating layer on the outside; S2: The carbon core that forms the oxygen transfer regulation layer on the outside in step S1 is dispersed in the ceramic skeleton shell precursor system. After stirring, drying and second heat treatment, a ceramic skeleton shell is formed on the outside of the oxygen transfer regulation layer, resulting in a shell-constrained pore-forming unit that includes a carbon core, an oxygen transfer regulation layer and a ceramic skeleton shell from the inside to the outside. The ceramic framework shell is not a single cerium oxide shell, but is composed of one or more of yttrium-stabilized zirconium oxide, alumina, mullite, yttrium aluminum garnet, or rare earth zirconates.
2. The method for preparing the shell-constrained pore-forming unit according to claim 1, characterized in that, The carbon core in S1 is one or more of the following: carbon microspheres, graphite microspheres, carbon black agglomerated particles, resin carbonized microspheres, or phenolic resin carbonized particles. The particle size of the carbon core is 1~30μm. The amount of carbon core added to the carbon core dispersion is 5~100g / L.
3. The method for preparing the shell-constrained pore-forming unit according to claim 1, characterized in that, The precursor salt in S1 is one or more of zirconium oxynitrate, zirconium oxychloride, zirconium acetate, cerium nitrate, cerium acetate, or yttrium nitrate; the total metal ion concentration of the precursor salt in the reaction dispersion system is 0.02~1.0 mol / L; based on the mass of the oxide theoretically formed in the first heat treatment of the precursor salt, the mass ratio of the oxide to the carbonaceous core is 0.05:1~1.5:1; the pH value of the reaction dispersion system is 8~10; the heating reaction temperature is 90~120℃, and the heating reaction time is 6~12h; the temperature of the first heat treatment is 300~450℃, and the time is 0.5~2h; the oxygen transfer regulating layer is one or more of cerium oxide, zirconium oxide, cerium-zirconium composite oxide, yttrium-stabilized zirconium oxide, doped cerium oxide, or doped zirconium oxide; the thickness of the oxygen transfer regulating layer is 0.05~1μm.
4. The method for preparing a shell-constrained porous unit according to claim 1, characterized in that, The ceramic framework shell precursor system in S2 is a combination of one or more of ceramic sol and ceramic nanoparticle dispersion; the ceramic sol is a combination of one or more of yttrium oxide-stabilized zirconia sol, alumina sol, silica sol, yttrium oxide sol, zirconia sol, lanthanum oxide sol, gadolinium oxide sol, samarium oxide sol, or ytterbium oxide sol; the ceramic nanoparticles in the ceramic nanoparticle dispersion are a combination of one or more of yttrium oxide-stabilized zirconia, alumina, mullite, yttrium aluminum garnet, or rare earth zirconate nanoparticles with an average particle size of 10-200 nm; in the ceramic framework shell precursor system, the dispersion... The phase content is 1-30% by mass, with the remainder being a dispersion medium; the carbonaceous core forming the oxygen transfer regulating layer on the outside is dispersed in the ceramic skeleton shell precursor system at a mass ratio of 1:0.1 to 1:5 between the carbonaceous core forming the oxygen transfer regulating layer on the outside and the ceramic solid components in the ceramic skeleton shell precursor system; the stirring, drying, and second heat treatment conditions are as follows: stirring for 0.5-12 hours, followed by drying at 60-120°C for 2-12 hours, and then a second heat treatment at 300-700°C for 0.5-4 hours; the thickness of the ceramic skeleton shell of the shell-constrained pore-forming unit is 0.2-5 μm.
5. The shell-constrained porous unit prepared by the method according to any one of claims 1 to 4, characterized in that, The shell-constrained pore-forming unit comprises, from the inside out, a carbonaceous core, an oxygen transfer regulating layer disposed outside the carbonaceous core, and a ceramic framework shell disposed outside the oxygen transfer regulating layer.
6. The method for preparing a zirconia-based thermal insulation coating using the shell-constrained pore-forming unit according to claim 5, characterized in that, Includes the following steps: (1) Preparation of composite granulated powder: The shell-constrained pore-forming unit, zirconia-based heat insulation powder, binder and solvent are dispersed together to form a spray granulation slurry. The spray granulation slurry is sprayed and granulated to obtain zirconia-based composite granulated powder containing shell-constrained pore-forming unit. (2) Spraying treatment: The zirconia-based composite granulated powder obtained in step (1) is fed into plasma spraying as a single composite spraying powder stream and deposited on the substrate surface to form a zirconia-based ceramic coating containing shell-constrained pore-forming units. (3) Staged heat treatment: The zirconia-based ceramic coating obtained in step (2) is subjected to staged heat treatment to obtain a zirconia-based heat insulation coating with closed-pore, semi-closed-pore or non-through-pore cavity structure.
7. The method for preparing the zirconia-based heat-insulating coating according to claim 6, characterized in that, The zirconia-based thermal insulation powder in step (1) is composed of one or more of yttrium-stabilized zirconia powder, cerium-stabilized zirconia powder, and rare earth zirconate powder; the yttrium-stabilized zirconia powder contains 6-8% Y₂O₃ by mass, with the remainder being ZrO₂ and unavoidable impurities; the spray granulation slurry contains 30-70% solids by mass, with the remainder being solvent; the solids content in the spray granulation slurry is the percentage of the total mass of the shell-constrained pore-forming unit and the zirconia-based thermal insulation powder to the total mass of the spray granulation slurry; with the total mass of the shell-constrained pore-forming unit and the zirconia-based thermal insulation powder being 100%, the mass percentage of the shell-constrained pore-forming unit is 1-10%, with the remainder being zirconia-based thermal insulation. The powder; the amount of binder added to the spray granulation slurry is 0.5-5% of the total mass of the shell-constrained pore-forming unit and the zirconia-based thermal insulation powder; the binder is not included in the solid content; the binder is one or more of polyvinyl alcohol, polyvinylpyrrolidone, or carboxymethyl cellulose; the dispersion method of the shell-constrained pore-forming unit, zirconia-based thermal insulation powder, binder, and solvent is one of drum premixing, low-energy ball milling premixing, wet dispersion, or slurry dispersion; the inlet air temperature of the spray granulation is 180-250℃, the outlet air temperature is 70-120℃, the atomization pressure is 0.2-1.0MPa, and the slurry feed rate is 5-100mL / min; the particle size of the resulting zirconia-based composite granulated powder is 15-100μm.
8. The method for preparing the zirconia-based heat-insulating coating according to claim 6, characterized in that, The plasma spraying power of step (2) is 20~45kW, the spraying distance is 80~120mm, and the powder feeding rate is 10~80g / min; the substrate is one of nickel-based alloy, iron-based alloy, titanium alloy or ceramic-based composite material; the staged heat treatment of step (3) includes a first stage oxidation pore-forming treatment and a second stage necking treatment; the temperature of the first stage oxidation pore-forming treatment is 400~750℃ and the time is 0.5~10h; the temperature of the second stage necking treatment is 700~1100℃ and the time is 0.5~5h.
9. The composite granulated powder prepared by the method according to any one of claims 6 to 7.
10. The zirconia-based heat-insulating coating prepared by the method according to any one of claims 6 to 8, characterized in that, The zirconia-based thermal insulation coating includes zirconia-based ceramic sheets and closed-cell, semi-closed-cell, or non-penetrating cavity structures distributed between and / or within the zirconia-based ceramic sheets. The cavity structures are constrained by a ceramic skeleton shell and / or zirconia-based ceramic sheets, and are formed by in-situ oxidation or removal of the carbonaceous core in the pore unit constrained by the shell. The cavity structures are not penetrating along the thickness direction of the zirconia-based thermal insulation coating. The ceramic skeleton shell material is retained around the pores, and a local sintering neck and / or interface closure region is formed between the ceramic skeleton shell and the adjacent zirconia-based ceramic sheets.